Opportunities of Digital Fabrication Laboratory Technology as Innovative Chemistry Pedagogical Tools: Trends and Pre-Service Chemistry Teachers’ Perspective - Anita Fibonacci; Asep Kadarohman; Hernani Hernani; Ika Nur Fitriani (Journal of Innovation in Educational and Cultural Research, 2024)
Fabrication laboratories transform an idea into a tangible product, making it a potential pedagogical tool in chemistry education. This research aimed to explore the potential aspects of the Fabrication Laboratory as a pedagogical tool in terms of existing literature and how pre-service chemistry teachers perceive the opportunities for the Fabrication Laboratory as a pedagogical tool for teaching chemistry to students. The study was conducted using descriptive research. A total of 54 pre-service chemistry teachers from a University in Central Java, Indonesia, were interviewed regarding their perspectives on the opportunities of Fabrication Laboratory to overcome difficulties in chemistry learning. The result showed that the Fabrication Laboratory has the opportunity to be a pedagogical tool for teaching chemistry to students in terms of existing literature and the views of pre-service chemistry teachers. The Fabrication Laboratory has the opportunity to be a pedagogical tool for teaching chemistry in terms of existing literature and the views of pre-service chemistry teachers. Several advantages that make FabLab have the potential as a pedagogical tool, according to pre-service chemistry teachers, include (a) flexibility of printed 3D chemistry media, (b) development creativity, and (c) technological innovation. This research provides implications for the professional development of pre-service chemistry teachers regarding the use of cutting-edge technology such as FabLab, which has a powerful tool for pedagogical transformation, especially for pre-service chemistry teachers in facing the challenges and opportunities of chemistry learning in the 4.0 revolution era.